Meningkatkan Profesionalisme Guru Kelas I Dan II Melalui Optimalisasi Pelaksanaan Supervisi Akademik Di Gugus Nakula V Kecamatan Serengan Kota Surakarta - Ismiyatun Ismiyatun (Universitas Muhammadiyah Surakarta, 2016)
This research aimed at increasing the teacher’s ability in making a lesson plan and conducting a learning process in the class. Type of this research is an Action Research. This research was conducted in 5 school areas of Gugus V Nakula of Serengan Sub-district, Surakarta. The location selection of this research was because the schools are under the guidance of the researcher, because from the results of observation, there were still many teachers who had not understood the main task and functions of a professional teacher. This research was conducted for three months from July 2011 to September 2011, starting from the preparation up to the reporting. Basically, the data which became the analysis materials were primary data that were through a direct observation obtained from the respondents by using the Instrument of Observation. The data consisted of data on the teachers’ ability in composing a syllabus and lesson plan (RPP), as well as implementing a learning in the class. The results of the research conclusion and discussion were as follows: 1) The giving of guidance in the beginning of composing the syllabus, the lesson plan, and the implementation of learning can optimize the results of supervision that was increasing the teachers’ professionalism. It could be viewed from the increase in the teachers’ ability from the early condition, cycle I and cycle II based on the data obtained by the researcher; 2) The Academic Supervision could increase the teachers’ ability in becoming professional teachers. From 13 teachers who became the researcher’ partners, their professional ability was increased significantly. In composing the lesson plan in the cycle I, from 13 teachers, all of them (100%) obtained scores under 90. Nevertheless, in cycle II, the scores of all teachers increased, therefore, only one teacher whose score was under 90 (7.69%). Similarly, in their ability of implementing the learning, in cycle I, only 2 teachers whose scores were above 80 (15%). Nevertheless, in cycle II, the teachers’ scores increased totally, only one teacher whose score was under 90.